Comparative Efficacy Evaluation of Microbial Consortia for Rapid Composting of Paddy Straw - Vellaichamy Mageshwaran; Pratyush Tripathi; Ashish K. Vishvakarma; Amit Yadav (Journal of Pure and Applied Microbiology)
The present study was aimed to evaluate five different microbial consortia for rapid composting of paddy straw and analyze the quality of compost produced. The experimental study on rapid composting of paddy straw was taken at ICAR-NBAIM, Kushmaur, Mau, Uttar Pradesh, India, during the period February to April 2022. The paddy straw was collected from the farm of ICAR-IISS, Mau, U.P., India and the collected paddy straw was chopped into 4-5 cm and further used for the study. The composting experiment was performed in bio-conversion bags of size [12 (L) x 4 (B) x 3 (H) feet]. There were six treatments in which five treatments were taken to evaluate five different microbial consortia and one control (no microbial consortium added). The five different microbial consortia tested were BIO-FAST, BIO-COMPOST, NCOF, PUSA and TEJAS. The results showed that Carbon-Nitrogen (C:N) ratio was reached to less than 20 at 60 days in BIO-FAST applied paddy straw followed by NCOF. While, the C:N ratio of control at 60 days was 33.71. Similarly, the primary nutrients (N, P and K) were higher (p < 0.05) in BIO-FAST followed by NCOF applied compost. The microbial activity and enzymatic activities were found to be insignificant (p < 0.05) in microbial consortia added treatments. The diluted extract of compost (50% and 20%) had higher germination index and no phytotoxicity effect. Thus, the results revealed that the addition of BIO-FAST accelerate the composting process and produce quality compost from paddy straw in 60 days.